The viability study of minimising operational costs: tyre, maintenance and fuel reference: Firstgain Holdings Sdn Bhd / Hafez Amri Sanusi - Sanusi, Hafez Amri (1995)
This paper was written to study the viability of minimising operational costs, namely; tyre, maintenance and fuel consumption, with reference to Firstgain Holdings Sdn Bhd., a subsidiary of Faber Haulage Sdn Bhd. The recommendation that being quoted will help Firstgain in solving the increasing operational costs that at present it is suffering. At present the variable costs which are in practice are not properly monitored and controlled. It is in this paper that the researcher tries to convince Firstgain the recommendation that is proposed can solve part of their problem and thus minimise the operating expenses. This paper covers all the important factors that resulted in the increasing costs and the solution to the problems. Information were obtained from formal and informal interviews and also personal observation as Primary Data collection and published materials, operation manual and academic books as Secondary Data collection.